(untitled) (Mustansiria Dental Journal, 2018)
Fracture or debonding of plastic teeth from the denture base are common clinical problems, the optimal combination of acrylic resin denture teeth and microware cured denture base resin is not well known .one hundred and twenty teeth (florident, acrylic teeth cross-linked, china) were prepared and cured by heat cured (AkrilEks, heatcuring resin for denture powder liquid, GuLSA LTD. Izmir-Turkey), and microware cured (Acron mc, microwave-curing denture base resin powder liquid, GCLAB Technologies inc. Alsip,IL60803 Japan) acrylic resin were used, then the teeth were divided into six groups and treated with different surface treatment, the first group received no further treatment(control); the second group treatment with diatoric preparation; the third group treated with thinner(Turpentine-DYNA CoAT, Thinner, Netherlands); the fourth group treated with tone(Propanone, Acetone, England 99% Purity-Analyer); the fifth group were diatoric conditioned with acetone; the sixth group were diatoric conditioned with thinner;(2nd group, 5th group and 6th group had been a cutting mesiodistal retention grooves 2mm deep and 3mm wide acute into ridge lap in acrylic resin teeth. One hundred and twenty specimens were divided into two groups, first one was processed by conventional method and the other one processed by microwave method and then tested by instron universal testing machine (instron corporation 1195,canton mass).The results showed than microwave-cured resin has a significant lower shear bond strength(SBS) mean values than water bathcured resin to all denture teeth types. All surface treatment application improved the(SBS) significantly level at(p value < 0.05), while the sixth group (diatoric conditioned with thinner) showed the highest(SBS) than other group. The types of acrylic denture resin, surface treatment and curing technique influenced the shear bond strength of the tooth to the base the results of this study influenced the shear bond strength of the tooth to the base. The results of this study indicate that diatoric condition with thinner may be recommended to be applied on the denture ridge lap prior to denture base processing.